The risk of pediatric bicycle handlebar injury compared with non-handlebar injury: a retrospective multicenter study in Osaka, Japan - Hirose, Tomoya (Scand J Trauma Resusc Emerg Med, 2015)
BACKGROUND: Bicycle accidents are one of the major causes of unintentional traumatic injury in childhood. The purpose of this study was to examine characteristics and risks of handlebar injury in childhood. METHODS: We conducted a more than 5-year retrospective survey of patients under 15 years of age with bicycle-related injuries admitted to eight urban tertiary emergency centers in Osaka, Japan. Patients were divided into the direct-impact handlebar injury (HI) group and the non-handlebar injury (NHI) group. RESULTS: The HI group included 18 patients and the NHI group included 308 patients. Median Injury Severity Score (ISS) in the HI group was 9. Injury sites included the chest, 2 (chest bruise, 1; tracheal injury, 1) and abdomen, 16 (hepatic injury, 6; pancreatic injury, 2; duodenal injury, 1; splenic injury, 1; small intestinal injury, 1; retroperitoneal hemorrhage, 1; renal injury, 1; abdominal wall musculature injury, 2; bladder injury, 1; and perineal laceration, 1). There were no significant differences in age, sex, ISS, and prognosis between the two groups. However, significant differences were seen in the abdominal median Abbreviated Injury Scale (AIS) score, which was higher in the HI group (3 vs 0, p < 0.01), and in the head median AIS score, which was higher in the NHI group (0 vs 2, p < 0.01). As mechanisms of injury, falling while riding a bicycle occurred significantly more frequently in the HI group (17 [94.4 %] vs 65 [21.1 %], p < 0.01). Direct transportation from the scene of the accident occurred significantly more often in the NHI group (5 [27.8 %] vs 255 [82.8 %], p < 0.01), whereas transfer from another hospital occurred significantly more frequently in the HI group (11 [61.1 %] vs 45 [14.6 %], p < 0.01). CONCLUSIONS: Handlebar injuries in children have significant potential to cause severe damage to visceral organs, especially those in the abdomen.